Professional Behavior Based on the Development of Employees - Sudarma, Ketut (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2014)
The objective of the study was to analyze the impact of work discipline management, career management and profession ethics management toward Unnes staffs behavior. The samples were taken by proportional random sampling. The variables of the research were work discipline management, career management, profession ethics management and professional behavior. The data were analyzed by multiple regression analysis. The result of this study showed that discipline work management, career management and profession ethics management gave positive influence toward staffs professional behavior. Furthermore, the result of percentage descriptive analysis showed that the average of work discipline management, career management, profession ethics management and professional behavior were on enough category.